E-Portfolio as an Early Childhood Assessment Tool in Kindergarten - Jhoni Warmansyah; Meliana Sari; Abdul Halif; Afriyane Ismandela; Dinda Fatma Nabila; Ravidah; Abdurrahman Niarman (Universitas Pendidikan Ganesha, 2022)
The various types of assessments that exist at the PAUD unit level require innovation to meet the demands of the times. In field observations, it was found that portfolio assessment was still manual, so it needed to be fully documented. This study aims to develop an early childhood assessment tool based on an e-portfolio in PAUD units. This type of research is development. The research method used is research and development (R&D) with a 4D model. This research only reached the development stage. The instrument used is the media feasibility test and the practicality test. The test subjects in this study were 20 kindergarten teachers. The resulting product has been validated by 3 material experts and 3 media experts. The methods used to collect data are interviews and questionnaires. The instrument used in collecting data is a questionnaire. The data analysis technique used is descriptive qualitative and quantitative analysis. The research results, namely the processing of the material feasibility test, obtained results of 90% and the media 91.67%. It was concluded that the e-portfolio device is valid and can be used, while for the practicality test, the results obtained were 85.86%, which means the device is practical to use.